Placental expressions of Anti-Mullerian hormone/Receptor, vascular endothelial growth factor and related microRNAs in patients with preeclampsia: a case control study - Hasdemir, Pinar Solmaz; Celikcekic, Didem; Oztatlici, Mustafa; Ozbilgin, Kemal (Biotechnic & histochemistry, 2024)
Anti-Mullerian hormone (AMH) has been implicated in the pathogenesis of preeclampsia. The present study was primarily designed to determine the placental tissue AMH, Anti-Mullerian hormone Receptor II (AMHRII), vascular endothelial growth factor (VEGF) and microRNA (miRNA) 26a/126/155/210 expressions and serum miRNA 26a/126/155/210 levels in patients with preeclampsia to examine their potential role in the pathogenesis of preeclampsia. Placental tissue samples from patients with preeclampsia (n = 20) and control subjects (n = 20) were examined by immunohistochemical staining and quantitative polymerase chain reaction (qPCR) for AMH, AMHRII, VEGF mRNA expression levels and miRNA 26a/126/155/210 expressions. Serum levels of miRNA 26a/126/155/210 were measured by qPCR. Patients with preeclampsia had lower AMH/AMHRII immunostaining, particularly in syncytiotrophoblastic cells compared to control subjects (p < 0.05). The relative mRNA expressions of AMH/AMHRII were increased (1.535 ± 0.121 and 1.155 ± 0.049 fold, p < 0.0002 and p < 0.033, respectively) and the relative mRNA expression of VEGF was decreased (4.878 ± 0.331 fold, p < 0.0002) in patients with preeclampsia compared to control subjects. The miR-26a expression was increased and miR-126 expression was decreased in serum samples of patients with preeclampsia compared to control subjects (p < 0.0002). miR-155 and miR-210 expressions were increased in serum and placental tissue samples of patients with preeclampsia compared to control subjects (p < 0.0002). In conclusion, reduced placental tissue immunostaining of AMH/AMHRII along with increased AMH/AMHRII mRNA expressions may indicate posttranscriptional dysregulation. Robust increase in expressions of hypoxia/inflammation-related miRNAs particularly miR-155 and miR-210 might have a role in this mechanistic pathway. Increased serum levels of miR 26a, 155 and 210 are potential early diagnostic markers for preeclampsia.